Evaluation of Adhesions Induced Intestinal Obstruction following Abdominal Penetrating Missile Injuries - Al-Atroshi, . Mohammed A.; Akram, Warqaa Mazin; Farouk, Bassam (AL-Kindy College Medical Journal, 2009)
Objectives: To evaluate the incidence of adhesions induced intestinal obstruction after explorative laparotomy due to bullet/shell injury in Al-Kindi teaching hospital/Baghdad. Results: Thirty-six out of the 76 cases with adhesions induced intestinal obstruction (A.I.I.O.) had history of laparotomy for penetrating missile injury, 26 of them were explored as a method of management of A.I.I.O. with mean age (22 for those explored, ٣٧ for those treated conservatively), 16 of them presented within a year or less from the previous surgery. Methods: Comparative interventional prospective study of cases with adhesions induced intestinal obstruction admitted to the surgical wards in Al-Kindi teaching hospital from the 1st of January 2008 to 31st of December 2008. cases were followed considering the indications of previous laparotomies, the patients age, gender, duration between previous surgery and their presentation with intestinal obstruction Conclusion: Cases required surgical interventions for treatment were mainly those following explorative laparotomy for penetrating missile injury they were mainly of young age Groups